Switching it up: The effect of energy price reforms in Oman. (June 2021) - Amann, Juergen; Cantore, Nicola; Calí, Massimiliano; Todorov, Valentin; Cheng, Charles Fang Chin
Abstract: For the most part the public debate on fossil fuel energy subsidies has been governed by two arguments. From the position of the profit-maximizing firm, the economic rationale has gravitated towards the issue of cost-competitiveness: The reduction of emissions requires a cutback of energy consumption which, when operating through the pricing mechanism, drives up the cost of inputs; increases in fossil fuel prices may therefore harm competitiveness. On the other hand, the environmental argument stresses the importance of cost transparency and externalities. However, there has also emerged a body of research which introduces a second layer to the argument of cost-competitiveness by emphazising that an increase in energy prices may not necessarily be detrimental to economic performance. This study provides novel evidence on this insight by examining the effect of a change in fossil fuel subsidies on the manufacturing industry of an oil-rich Middle Eastern economy. Using a novel firm-level micro data set on Omani manufacturing enterprises, our work shows that increases in fossil fuel energy factor prices lead to improvements in productivity as well as efficiency and notable business upgrading. The findings in this paper indicate that subsidy reforms may not only be used to achieve environmental goals but may also drive upgrading and modernization processes of firms that can, ultimately, also improve economic performance.